1988
DOI: 10.1128/aem.54.12.3177-3179.1988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inorganic nutrients on the acclimation period preceding mineralization of organic chemicals in lake water

Abstract: The addition of phosphate, nitrate, or sulfate (each at 10 mM) decreased the acclimation period for the mineralization of low concentrations of p-nitrophenol (PNP) in lake water. Added phosphate shortened the acclimation period for biodegradation of 2 ng to 2 ,ug of PNP per ml in various lake water samples and of 2,4-dichlorophenoxyacetate at 100 ng/ml. Added P enhanced the rate of growth of PNP-mineralizing microorganisms in waters containing 200 ng or 2 ,ug of PNP per ml. We suggest that the effect of P on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Phosphate or nitrogen was a limiting factor for the degradation of DCP at low concentrations in the groundwater. These observations coincide with the study done by Jones & Alexander,6) who have reported that a rapid mineralization of p-nitrophenol (PNP) by Flavobacteriurn sp. proceeded when sterile lake water was amended with 10mM of P04-P, and initiation of mineralization was delayed when water samples received zero, 0.01, or 0.1mM P04-P.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphate or nitrogen was a limiting factor for the degradation of DCP at low concentrations in the groundwater. These observations coincide with the study done by Jones & Alexander,6) who have reported that a rapid mineralization of p-nitrophenol (PNP) by Flavobacteriurn sp. proceeded when sterile lake water was amended with 10mM of P04-P, and initiation of mineralization was delayed when water samples received zero, 0.01, or 0.1mM P04-P.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to these fresh waters, the half-life of 4-nitrophenol in sea water may be longer, and the experimental half-life may range between 13 and 21 days (Bourquin et al 1982;Bourquin 1984;. The rate and extent of degradation of 4-nitrophenol in natural water also depend on the initial concentration of the substance, the nature and concentration of nutrients, the activities of the organisms, and the presence or absence of predators or inhibitors of degrader organisms (Hoover et al 1986;Jones and Alexander 1988;Rubin and Alexander 1983;Wiggins and Alexander 1988;Zaidi et al 1989). Other investigators have found that the rate of biodegradation of nitrophenols may follow complex kinetics and the derivation of a half-life based on simple first-order kinetics in such cases would not be appropriate Alexander 1986, 1988;Zaidi et al 1988).…”
Section: Watermentioning
confidence: 99%
“…Effect of nutrients on acclimation [9,10] Acclimation processes for individual or classes Effect of chemical concentration [12,14,15] Biodegradation of dissolved and adsorbed chem-Importance of attached or unattached bacteria…”
mentioning
confidence: 99%